The effect of market trends and customer relationship management for performance in microfinance institutions of developing countries - Alabdan, Rusul Hisham; Zainuddin, Y. (URBE, 2022)
This study examined performance management in the context of microfinance institutions in low-income countries. First, it did a deep dive into the implications of performance management systems in low-income settings. Second, a review of the theoretical and conceptual frameworks of management systems for numerous types of performance was undertaken to better understand the various performance management systems for microfinance institutions in developing countries. Third, we examine how financial institutions in a few nations manage their institutions' performance and how the direction of trends affects the expansion of those institutions. Finally, the study highlights the conclusions and gaps in the research that were revealed. The first section of this article focuses on the significance of context, which is the interaction between the extrinsic aspects (such as customer relationship management and market trend orientations) with which microfinance institutions work. We have examined both the internal and external elements that determine the success of a microfinance institution (MFI).